Constraints to growth of small and medium enterprises in Zanzibar: The case of urban west region - Hassan, Zena M. (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the degree of Master of Science in Economics (economic policy and planning) of Mzumbe university